UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN JERUK PURUT (Citrus hystrix (D.C)) TERHADAP BAKTERI Propionibacterium acnes - Fitriyanti Fitriyanti; Muhammad Hafizudin; Muhammad Nazarudin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Lime leaves contain flavonoids, tannins, saponins and steroids which are thought to have antibacterial activity. This study aimed to determine the antibacterial activity of the methanol extract of Lime leaves to P.acnes bacteria and to determine the activity of methanol extract of the leaves of Lime based on the value of the diameter of the inhibitory zone and the inhibition category. Lime Leaves extracted by the maceration method using methanol solvent followed screening tests phytochemical. The antibacterial activity test was carried out by the sump method with 6 concentrations of methanol extract of the leaves of Lime according to 25mg/mL, 50mg/mL, 100mg/mL, 200mg/ mL, 300mg/mL and 400mg/mL, positive control of clindamycin 0,1% and negative control Na-CMC 0,5%. The results of phytochemical screening, methanol extract positively contain flavonoids, saponins, tannins, and steroids. Antibacterial test results showed that the inhibition zone of the Lime leaves of the methanol extract in the concentration of 25 mg/ml, and 50 mg/mL was 8.35 and 9.4 mm (medium category), concentrations of 100 mg/ml, and 200 mg/mL were 11.77, and 19.45 mm (strong category), and concentrations of 300mg / ml, and 400mg/mL, namely 21.05, and 22.87 mm (very strong categories). SPSS test results there were significant differences between treatment groups (sig <0.05).